Lorentz boost of nuclear form factors (2024)
The Lorentz boost of Form Factors provides one of the solution to the discrepancies found on the measurements of the nuclear charge radius of the proton from scattering and atomic physics. This document intends to extend this solution to some light nuclei in order to explore its implications, limitations and the accuracy of different formalisms. Starting with a short review on the electromagnetic form factors, seen from its theoretical background based on Quantum Field Theory, some approaches to obtain closed formulas from other arguments and experiments are presented. One of the main applications of the form factors is to find nuclear radii and apart drom this we explore other methods ox extracting the nuclear radii. The basic idea, properties and limitations behind the many methods are also explored. Also, we introduce each of the formalisms used to obtain the Lorentz boosted Form Factor and, by means of the method presented at the end of the first section, a general correction to the value of the nuclear charge radii is obtained to link the values from scattering and atomic physics. Finally, a general analysis of the correction is done, including the corrected values of radii obtained using the different formalisms for the lightest nuclei and mesons allowing a general evaluation of the formalisms and applications. The approaches for the Lorentz boost studied here show a dependency on the number of clusters in a nucleus or hadron to be different. The latter, along with data on scattering and atomic physics experiments allowed us to comment on the cluster structure of the nuclei and hadrons studied here.